The law on artificial insemination: an italian anomaly - cecchi, rossana; Masotti, Vittoria; Meo, Arturo Umberto; Rinaldi, Raffaella (Acta Biomedica Atenei Parmensis, 2018)
The law on medically assisted procreation in Italy, from its entering into force, has undergone numerous amendments. This has been due to the fact that those citizens, directly affected by its imposed prohibitions, have not given in, bringing their requests before the courts, both nationally and internationally. Over the years, the courts through numerous rulings have significantly changed a law clearly incapable of protecting the rights of those involved. Currently Italy has an acceptable law on M.A.P. which is the result of the strong willing of citizens affected by problems of sterility or infertility. The aim of this paper is to present an historical summary of the troubled path which the issue, from every perspective, has faced and is still facing today. As well, it will document how, in Italy, the case-law and, therefore, the law’s interpretation and application by the judges have contributed, in the end, to shaping a positive legislation.